Continuous production of iron oxide nanoparticles via fast and economical high temperature synthesis. Issue 8 (6th July 2020) - Besenhard, Maximilian O.; LaGrow, Alec P.; Famiani, Simone; Pucciarelli, Martina; Lettieri, Paola; Thanh, Nguyen Thi Kim; Gavriilidis, Asterios
Abstract : A continuous, fast and economical high temperature synthesis of iron oxide nanoparticles was developed and compared to a conventional batch synthesis in terms of production costs. Abstract : From all of the iron oxide nanoparticle (IONP) syntheses, thermal decomposition methods are the most developed for controlling particle properties, but suffer from poor reproducibility at larger scale. An alternative solution for large scale production is continuous synthesis, where the production volume can be increased with longer operation times. However, continuous thermal decomposition synthesis is not trivial as it requires oxygen and water removal from the precursor solution, reaction temperatures above 230 °C, and the formation of particles is likely to cause reactor fouling. This work presents a continuous thermal decomposition synthesis of IONPs using a tubular flow reactor, which provides inert reaction conditions at temperatures of up to 290 °C, and heating/cooling at rates which cannot be achieved in standard batch systems. This makes it possible to define the start and endpoint accurately, hence, allowing for a well-controlled and scalable thermal decomposition synthesis. A simple synthetic protocol was chosen using only ferric acetylacetonate, oleylamine, and 1-octadecene as a solvent, but no additives to minimise costs. In this flow reactor residence times of less than 10 min were shown to be sufficient to synthesise monodisperse IONPs of 5–7 nm and achieve precursor conversion between 10–70% depending on the reaction temperature. For all synthesis conditions tested, there was no indication of reactor fouling. Since the precursor conversion correlated to the residence time and reaction temperature, but particle sizes were comparable for all reaction conditions studied, the particle formation is proposed to follow mechanisms other than classical nucleation and growth. To examine possible economic advantages of such a continuous thermal decomposition process as compared to a conventional batch synthesis, a cost analysis, comparing costs assigned to chemicals, reactor equipment, energy and labour, was performed.